Long-Range RNA-RNA Interactions Circularize the Dengue Virus Genome - Alvarez, Diego Ezequiel (2005)
Secondary and tertiary RNA structures present in viral RNA genomes play essential regulatory roles during translation, RNA replication, and assembly of new viral particles. In the case of flaviviruses, RNA-RNA interactions between the 5′ and 3′ ends of the genome have been proposed to be required for RNA replication. We found that two RNA elements present at the ends of the dengue virus genome interact in vitro with high affinity. Visualization of individual molecules by atomic force microscopy reveled that physical interaction between these RNA elements results in cyclization of the viral RNA. Using RNA binding assays, we found that the putative cyclization sequences, known as 5′ and 3′ CS, present in all mosquito-borne flaviviruses, were necessary but not sufficient for RNA-RNA interaction. Additional sequences present at the 5′ and 3′ untranslated regions of the viral RNA were also required for RNA-RNA complex formation. We named these sequences 5′ and 3′ UAR (upstream AUG region). In order to investigate the functional role of 5′-3′ UAR complementarity, these sequences were mutated either separately, to destroy base pairing, or simultaneously, to restore complementarity in the context of full-length dengue virus RNA. Nonviable viruses were recovered after transfection of dengue virus RNA carrying mutations either at the 5′ or 3′ UAR, while the RNA containing the compensatory mutations was able to replicate. Since sequence complementarity between the ends of the genome is required for dengue virus viability, we propose that cyclization of the RNA is a required conformation for viral replication.